Biofilm Formation of Staphylococcus aureus from Pets, Livestock, and Wild Animals: Relationship with Clonal Lineages and Antimicrobial Resistance - Vanessa Silva; Elisete Correia; José Eduardo Pereira; Camino González-Machado; Rosa Capita; Carlos Alonso-Calleja; Gilberto Igrejas; Patrícia Poeta (MDPI AG, 2022)
This study aimed to compare the biofilm formation ability of Staphylococcus aureus isolated from a wide range of animals and study the association between biofilm formation and antimicrobial resistance and genetic lineages. A total of 214 S. aureus strains isolated from pets, livestock, and wild animals were evaluated regarding their ability to form biofilms by the microtiter biofilm assay and their structure via confocal scanning laser microscopy. Statistical analysis was used to find an association between biofilm formation and antimicrobial resistance, multidrug resistance, sequence types (STs), spa and agr-types of the isolates. The antimicrobial susceptibility of 24 h-old biofilms was assessed against minimum inhibitory concentrations (MIC) and 10× MIC of amikacin and tetracycline, and the biomass reduction was measured. The metabolic activity of biofilms after antimicrobial treatment was evaluated by the XTT assay. All isolates were had the ability to form biofilms. Yet, significant differences in biofilm biomass production were detected among animal species. Multidrug resistance had a positive association with biofilm formation as well as methicillin-resistance. Significant differences were also detected among the clonal lineages of the isolates. Both tetracycline and amikacin were able to significantly reduce the biofilm mass. However, none of the antimicrobials were able to eradicate the biofilm at the maximum concentration used. Our results provide important information on the biofilm-forming capacity of animal-adapted S. aureus isolates, which may have potential implications for the development of new biofilm-targeted therapeutics.